2022
DOI: 10.4196/kjpp.2022.26.6.501
|View full text |Cite|
|
Sign up to set email alerts
|

Thermotherapy as an alternative to exercise for metabolic health in obese postmenopausal women: focus on circulating irisin level

Abstract: Irisin is a myokine caused by exercise that improves insulin resistance and weight loss. However, under unfavorable conditions such as air pollution, and during the pandemic, outdoor activities are uncomfortable. Therefore, in this study, the effect of heat therapy (half bath 42 ± 0.5°C for 30 min) on irisin circulation levels as an exercise alternative for middle-aged obese women after menopause was investigated. Subjects were 33 women aged 49.54 ± 6.04 years, with parameters of height, 160.12 ± 4.33 cm, weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Injections of recombinant irisin, or a modified version of the peptide, would increase accessibility to irisin therapies, especially for those with later-stage MetS causing reduced mobility. Additional exercise-independent methods of stimulating irisin secretion may also be considered, and for example, a regular weekly thermotherapy regimen of intermittent heat exposure by bathing increased plasma irisin and basal metabolic rate, and decreased waist circumference and body fat percentage in postmenopausal women ( 101 ). Furthermore, some existing drugs targeting component conditions of MetS, including metformin, simvastatin and exenatide, may upregulate skeletal muscle FNDC5 expression and/or increase plasma irisin concentrations ( 102 ).…”
Section: Discussionmentioning
confidence: 99%
“…Injections of recombinant irisin, or a modified version of the peptide, would increase accessibility to irisin therapies, especially for those with later-stage MetS causing reduced mobility. Additional exercise-independent methods of stimulating irisin secretion may also be considered, and for example, a regular weekly thermotherapy regimen of intermittent heat exposure by bathing increased plasma irisin and basal metabolic rate, and decreased waist circumference and body fat percentage in postmenopausal women ( 101 ). Furthermore, some existing drugs targeting component conditions of MetS, including metformin, simvastatin and exenatide, may upregulate skeletal muscle FNDC5 expression and/or increase plasma irisin concentrations ( 102 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adolescence is a stage of neurodevelopmental period characterized by pronounced neuroplasticity and significant structural and functional changes in the brain, particularly in regions associated with advanced cognitive function [ 1 , 2 ]. While physical activity is essential for healthy development [ 3 ] during adolescence, the practice of walking has become less common in modern societies [ 4 ]. This is concerning as research has demonstrated that regular physical activity, including walking, can have significant physiological and psychological benefits for adolescents [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%